Little Tigers Big Surprise - Julie Sykes & Tim Warnes
Little Tiger isn't happy when Mommy Tiger tells him he will soon have a little brother or sister. He isn't good with change and likes things the way they are. Can anyone persuade him that a new cub can be lots of fun?! Wonderfully illustrated and highly engaging with a great story for all children to enjoy.